34 inspirasi Ruang bawah tangga / Lubab, Ira Humairo, Rizky Ananda Putri Inaray ; editor Luthfi kurniawan - LUBAB; Ira Humairo; Rizki Ananda Putri Inaray; Luthfi Kurniawan (Griya Kreasi, 2014)
115 hlm : ilus ; 22 cm [3 eks]